Increased blood flow prevents intramucosal acidosis in sheep endotoxemia: a controlled study - Dubin, Arnaldo (2005)
Introduction Increased intramucosal–arterial carbon dioxide tension (PCO₂) difference (∆PCO₂) is common in experimental endotoxemia. However, its meaning remains controversial because it has been ascribed to hypoperfusion of intestinal villi or to cytopathic hypoxia. Our hypothesis was that increased blood flow could prevent the increase in ∆PCO₂. Methods In 19 anesthetized and mechanically ventilated sheep, we measured cardiac output, superior mesenteric blood flow, lactate, gases, hemoglobin and oxygen saturations in arterial, mixed venous and mesenteric venous blood, and ileal intramucosal PCO₂ by saline tonometry. Intestinal oxygen transport and consumption were calculated. After basal measurements, sheep were assigned to the following groups, for 120 min: (1) sham (n = 6), (2) normal blood flow (n = 7) and (3) increased blood flow (n = 6). Escherichia coli lipopolysaccharide (5 µg/kg) was injected in the last two groups. Saline solution was used to maintain blood flood at basal levels in the sham and normal blood flow groups, or to increase it to about 50% of basal in the increased blood flow group. Results In the normal blood flow group, systemic and intestinal oxygen transport and consumption were preserved, but ∆PCO₂ increased (basal versus 120 min endotoxemia, 7 ± 4 versus 19 ± 4 mmHg; P < 0.001) and metabolic acidosis with a high anion gap ensued (arterial pH 7.39 versus 7.35; anion gap 15 ± 3 versus 18 ± 2 mmol/l; P < 0.001 for both). Increased blood flow prevented the elevation in ∆PCO2 (5 ± 7 versus 9 ± 6 mmHg; P = not significant). However, anion-gap metabolic acidosis was deeper (7.42 versus 7.25; 16 ± 3 versus 22 ± 3 mmol/l; P < 0.001 for both). Conclusions In this model of endotoxemia, intramucosal acidosis was corrected by increased blood flow and so might follow tissue hypoperfusion. In contrast, anion-gap metabolic acidosis was left uncorrected and even worsened with aggressive volume expansion. These results point to different mechanisms generating both alterations.